Party Finance and Perceived Party Responsiveness - Lobo, Marina Costa (2018)
This chapter investigates an important implication of the cartel party thesis: that parties’ shift from society towards the state has eroded voters’ sense of political efficacy. More precisely, it explores whether and to what extent parties’ financial dependence on the state shapes electors’ feelings about the responsiveness of parties. The authors do this by linking PPDB (Political Party Database) information with the Comparative Study of Electoral Systems (CSES) data. The results of their analysis show that the relationship between level of state funding of parties and citizens’ perceptions of party responsiveness is positive, though not strong. This is contrary to the theoretical expectations suggested by the cartel thesis, in that electors voting for parties more dependent on the state are not more likely to have low feelings of political efficacy.